Sulukule Transition: Impact on Municipal Destigmatization and Stigma Stickiness - Zuhal Güler; Betül Duman Bay (Journal of Economy Culture and Society)
This research article revisits the ‘Sulukule’ through the lens of destigmatization, where territorial stigma intersects with Roman ethnicity.’ With reference to socio-spatial developments, this article unpacks the soft and hard components of destigmatization, from displacement to neighborhood renaming, and discusses its design and implementational shortcomings. Future socio-spatial change is the aim of municipalities’ planning anddesignpractices. Basedonourobservationsfromthe2018field survey in Sulukule, we argue that the neighborhood’s negative reputation persists, rendering it "ungentrifable." Consequently, the neighborhood developed its own spatial and social dynamics over time rather than producing the municipality’s planned outcomes. The return of displaced Romani, the uncontrolled influx of refugees, rising tensions between non-Romani and Romani residents in Sulukule, and the flight of local middle-class residents to other districts all affected the outcome. In this context, we identified several flaws, such as the removal of territorial stigma and subsequent neglect of its overlapping nature; policy conflicts at both the central and local scales; and the prevalence of centralist and top-down urban governance. Directly addressing territorial destigmatization as a goal in all official documents and making those documents tangible through negotiations among stakeholders should be integral to the destigmatization process.